PENGELOLAAN APLIKASI PENILAIAN KINERJA GURU DI SMK NEGERI 2 SRAGEN BERBASIS WEB - Wawan Yulianto (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2018)
Abstrak Wawan Yulianto. The research’s aims are for 1) making web application to easy in online evaluation of the teacher performance in SMK Negeri 2 Sragen; and 2) knowing the suitableness of web application system on teacher performance evaluation in SMK Negeri 2 Sragen. The study is using research and development ( Research and Development / R&D ). The data collection used are interviews, questionnaires, observation and documentation. The suitableness quality of web application is tested by alpha and beta testing. Alpha testing is done by asking for opinion and validated by ITC (Information Technology Communication) experts and PKG content material experts, while beta testing is done by asking the users’ opinion, junior teachers, who are evaluated on on PKG. The suitableness data analysis is used Likert scale which is analyzed quantitatively and showed in percentage form. The results of the study are 1) PKG application in SMK Negeri 2 Sragen is developed trough some steps, they are ; introduction evaluation ( demand analysis and information collection); making and developing the former product / web application ( designing the former product, validating the design, and revising the product ); trying and error and revising the product ( both restrictively and widely ) until gaining the final product. 2) PKG application web in SMK Negeri 2 Sragen has gained the suitableness from the ICT team, PKG content material expert as well as from the users, the junior teacher, who are evaluated on PKG online Keywords :management, teacher performance evaluation, web